Screening of new potential carbon source for bioprotein production - Tompang, Mohamad Fahrurrazi; Jamal, Parveen; Alam, Md. Zahangir (2008)
This research was carried out to increase the availability of high quality affordable proteins by fermentation of agricultural wastes, which is one of the most promising breakthroughs of biotechnological innovations. Screening study was done to obtain the most potential substrate from agricultural wastes such as pineapple, honeydew and durian skins as main carbon source for bioprotein production. Liquid state bioconversion was done by using a previously screened potential and safe microbial strain P. chrysosporium. In this study, the effect of wheat flour concentration as co-substrate, which will surely reduce the cost of production. The fermentation was carried out without additional nutrient (WON) and with additional nutrient (WN). Pineapple akin showed a significant amount of protein production (72.9 g kg^-1) without wheat flour as co-substrate on the fourth day of fermentation with controlled process conditions of temperature of 32 degree celcius; agitation of 150 rpm; pH of 4.5 and 2% (v/v) inoculum. Bioprotein from local agro-waste can be a good source of supplement and additive in the animal feed as well as additives in the chemical and pharmaceutical products.